Periodic Comprehensive Forest Inventory on Production Forest Management in Papua Province - Financio Dorebayo; Endang Suhendang; Muhdin Muhdin (Jurnal Manajemen Hutan Tropika, 2015)
The Periodic comprehensive forest inventory (Inventarisasi Hutan Menyeluruh Berkala called IHMB) is Indonesian forest stands inventory were based on compartment at forest effective area of forest management unit (FMU). To preserve sustainable forest management, IHMB implementation are used as a benchmark on the determinate of maximum cutting area and large of timber volume that can be produced by FMU to preparing long-term forest planning. The purpose of this study is to assess the suitability and accuracy of the IHMB implementation results to arranging forest management plan that aims to produce sustainable timber. Data gathered with direct observation on FMU (PT. Bts and PT. SMS) in Papua Province. Data analysis using descriptive statistic method and the sampling is using purposive sampling method. The study showed that the data and information collected in accordance with IHMB guidelines have not covered all the necessary data to arranged forest management plans based on the sustainability forest principles to appropriate with the criteria and indicators of sustainability. IHMB Implementation is the important activity on FMU. The sense of word “comprehensive” on IHMB is meaningfully only covered the forest area, without including all components of the data and information on forest ecosystem..